2018
DOI: 10.3393/ac.2017.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Gland Attenuation, a Novel Morphological Feature of Colorectal Cancer: Evidence for an Epithelial-Mesenchymal Transition

Abstract: PurposeAlong the invasive margin, colorectal cancer may show distinctive morphologic changes characterized by an asymmetrically attenuating tumor gland with loss of polarity. The author coined the term ‘gland attenuation (GA)’ for these peculiar changes. The aims of this study were to compare the immunoreactivity of the epithelial-mesenchymal transition (EMT) markers E-cadherin and β-catenin and thus determine whether EMTs occurs at tumor budding (TB) or GA sites and to assess the association of TB and/or GA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…EMT is recognized to be important in cancer cell migration/metastasis. For example, to metastasize, disseminated mesenchyme-like tumor cells of well-differentiated carcinomas must regain their epithelial function (invasion and metastasis) [ 28 , 29 ]. The disruption of epithelial-cell homeostasis leading to aggressive cancer progression is correlated with the loss of epithelial characteristics and the acquisition of a migratory phenotype, known to EMT, and is considered to be a crucial event in malignancy [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is recognized to be important in cancer cell migration/metastasis. For example, to metastasize, disseminated mesenchyme-like tumor cells of well-differentiated carcinomas must regain their epithelial function (invasion and metastasis) [ 28 , 29 ]. The disruption of epithelial-cell homeostasis leading to aggressive cancer progression is correlated with the loss of epithelial characteristics and the acquisition of a migratory phenotype, known to EMT, and is considered to be a crucial event in malignancy [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence has revealed that FUT8 serves as a regulator in EMT through catalysing glycosylation. EMT is a process of epithelial cells converting into motile mesenchymal cells, which contributes pathologically to cancer migration, invasion and metastasis . Cell–cell adhesion mediated by E‐cadherin was strengthened with the reduction of core fucosylation, suggesting that blockade of FUT8‐mediated glycosylation can maintain cancer cell–cell connection.…”
Section: Discussionmentioning
confidence: 99%